2001
DOI: 10.1089/109264201750162257
|View full text |Cite
|
Sign up to set email alerts
|

Is Helium Insufflation Superior to Carbon Dioxide Insufflation in Bacteremia and Bacterial Translocation with Peritonitis?

Abstract: Helium might be an alternative to CO2 insufflation in patients with peritonitis if these results are confirmed by further experimental and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Study in rats showed that pneumoperitoneum causes intestinal ischemia with oxygen free radical production and bacterial translocation, related to mechanical pressure of CO 2 17 . Other studies focused on whether a pneumoperitoneum amplifies the extent and severity of peritonitis or of bacteremia in various animal models 18,19,20,21 . Findings from these investigations are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Study in rats showed that pneumoperitoneum causes intestinal ischemia with oxygen free radical production and bacterial translocation, related to mechanical pressure of CO 2 17 . Other studies focused on whether a pneumoperitoneum amplifies the extent and severity of peritonitis or of bacteremia in various animal models 18,19,20,21 . Findings from these investigations are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Some studies have shown that increased intraabdominal pressure via pneumoperitoneum may lead to the increased risk of bacterial translocation and bacteremia. [15][16][17][18][19][20][21][22][23][24][25][26] Some studies have shown that CO 2 has immunosuppressive effects on neutrophil and macrophage function, and CO 2 -induced immunosuppression might be deleterious in the setting of infection. [27,28] It has been argued as well that CO 2 pneumoperitoneum may cause malignant hypercapnia and toxic shock syndrome in the cases with peritonitis.…”
mentioning
confidence: 99%